2022
DOI: 10.1007/s11249-022-01635-x
|View full text |Cite
|
Sign up to set email alerts
|

High Friction Mechanism of ZDDP Tribofilm Based on in situ AFM Observation of Nano-Friction and Adhesion Properties

Abstract: Zinc dialkyl dithiophosphate (ZDDP) is a typical anti-wear additive that forms tribofilm on sliding surfaces and prevents adhesion wear but increases the friction force. In this study, the nano-friction and adhesion properties of ZDDP tribofilms were investigated by performing in situ observations by atomic force microscopy to explore the relationship between the formation process and physical properties of ZDDP tribofilm. The results showed that the nano-friction force increased with the formation of the ZDDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Tomale et al reported that the development of ZDDP tribofilm amplifies the adhesion force [61]. Kaisei et al also reported that the friction may increase because of the higher adhesion property of ZDDP [62]. These analyses also support the results in the current study; COF increased with ZDDP addition.…”
Section: Change In Surface Adhesion and Analysis Of Phase Profilesupporting
confidence: 89%
“…Tomale et al reported that the development of ZDDP tribofilm amplifies the adhesion force [61]. Kaisei et al also reported that the friction may increase because of the higher adhesion property of ZDDP [62]. These analyses also support the results in the current study; COF increased with ZDDP addition.…”
Section: Change In Surface Adhesion and Analysis Of Phase Profilesupporting
confidence: 89%
“…The differences shown are clearest as the lubrication regime worsens at top and bottom dead centre reversals indicating differences in interfacial boundary friction responsible for the variation in performance. It has been shown that thick phosphate ZDDP derived tribofilms on steel surfaces increase friction through roughening [37] and increased interfacial boundary shear stress [38,39]. However, it has previously been shown that ZDDP does not form thick tribofilms on Si-C and DLC surfaces, and that these films reduce friction on these non-ferrous surfaces Ueda et al [18], and Topolovec-Miklozic et al [40] have shown organic friction modifiers have little effect on friction on some non-ferrous surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high friction behavior of the ZDDP tribofilm has been consistently observed at the macroscale, irrespective of the sliding pair [18,26]. Kaisei Sato [27] utilized in situ Atomic Force Microscopy (AFM) to investigate the mechanism behind this high friction. Their studies revealed a significant correlation between the adhesion and nano-friction force, highlighting the substantial role played by the strong adhesion force of ZDDP tribofilm in generating elevated friction.…”
Section: Introductionmentioning
confidence: 99%